The Foreign Learners' Difficulties in English Speaking and How to Solve the Problems - Sabariyanto Sabariyanto (Indonesian Journal of Instructional Media and Model, 2021)
The objectives of this research are (1) to describe the difficulties faced by foreign learner in English Speaking; and (2) to describe the foreign learner’s solutions to solve the difficulties faced in English speaking. The design of this research is a descriptive qualitative research.The result of this research showed that foreign learners did face difficulties in performing English conversation. The difficulties were categorized into four points, in accordance with Penny Ur’s theory: inhibition, nothing to say, low or uneven participation, and mother-tongue use. For the solutions to resolve the difficulties, there are four poins, in accordance with Jeremy Harmer’s theory: preparation, repetition, big groups small groups, or mandatory participation. And the foreign learners used improvising strategy by Jeremy Harmer, also to help themselves develop the speaking ability, foreign learners used repetition strategy by Jeremy Harmer as well.